2006
DOI: 10.1038/sj.jhh.1002050
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of a study to evaluate management of proteinuria in patients at high risk for vascular events: the IMPROVE trial

Abstract: Declining kidney function predicts increasing cardiovascular risk in people with hypertension. Microalbuminuria is a marker for cardiovascular risk and declining kidney function. Agents that block the renin-angiotensin-aldosterone system (RAAS), notably angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs), reduce proteinuria and microalbuminuria, lower blood pressure and slow the progression of proteinuric kidney disease. Evidence is accumulating that the combination of an AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…of 0.73 used in the planning of the study. 22 Results for the two secondary, supportive analyses were consistent with the primary efficacy analysis. No earlier postrandomization data were collected for the first of these analyses and in the second, the inclusion of subjects with an AER of o20 mg/min had no significant effect on the results.…”
Section: Efficacysupporting
confidence: 56%
See 1 more Smart Citation
“…of 0.73 used in the planning of the study. 22 Results for the two secondary, supportive analyses were consistent with the primary efficacy analysis. No earlier postrandomization data were collected for the first of these analyses and in the second, the inclusion of subjects with an AER of o20 mg/min had no significant effect on the results.…”
Section: Efficacysupporting
confidence: 56%
“…Providing similar blood pressure, control was achieved in both treatment groups; it was assumed that any difference that emerged with respect to reductions in albuminuria would likely reflect differences in the therapeutic model of RAAS blockade working independently of blood pressure control. 22 As our results show, the study failed to meet its primary end point. It is important to stress that the study had a number of limitations, not least the fact that the study ended up being underpowered-despite careful planningand that it failed to recruit patients with high levels of albuminuria.…”
Section: Discussionmentioning
confidence: 81%
“…The combination of an ACE inhibitor and an ARB has demonstrated improvement in proteinuria and reduction in the progression to ESRD, compared with ACE inhibitor or ARB monotherapy in nondiabetic renal disease 20 . Similar studies are ongoing, using similar combinations in diabetic and nondiabetic proteinuria 27 . Other studies have shown the benefit of combination therapy on cognition with the ACE inhibitor perindopril plus the diuretic indapamide 28 .…”
Section: Combination Therapy Optionsmentioning
confidence: 98%
“…All diabetics subjects should undergo screening for microalbuminuria, in order to detect the earliest signs of diabetic nephropathy [22]. There are substantial observational data regarding the association between urinary albumin excretion and increased CVD risk and mortality in people with diabetes and hypertension [22][23][24].…”
Section: Microalbuminuriamentioning
confidence: 99%